A need for legal Framework on sexual offences against elderly woman in Malaysia - Mohamad Yunus, Mohamad Ismail (Sweet and Maxwell, 2017)
Recently the Parliament has approved the Sexual Offences Against Children Bill 2017, to protect anyone less than 18 years from sexual crimes. It is observed that like child sexual crimes, elder sexual crime is also a problem in our society to which attention must be given, and the victims of this ‘crime’ must also be given protection and the offenders must be punished accordingly. The objective of this article is to formulate a legal framework to legally recognise this offence as a specific crime and to find solutions to the issue, particularly in Malaysia, by studying the laws of other jurisdictions which have already introduced laws regarding the matter. The Islamic point of view in this matter is also be highlighted.